KINETIKA BIOSORPSI Cr(VI) DALAM LARUTAN MENGGUNAKAN BIOMASSA Phanerochaete chrysosporium - Soeprijanto Soeprijanto (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
The aims of this research were to study the ability of Phanerochaete chrysosporium biomass to adsorb metal ion of Cr(VI), to obtain equilibrium data concentrations and biosorption kinetics. P. chrysosporium was incubated in a sterilized liquid media of peptone 12.5 g/L and 50 g/L glucose at 35oC for 6 days. The obtained biomass culture was treated with NaOH 0.5 N, and then boiled for 15 minutes. A variety of biomass concentrations were mixed with 200 mg Cr(VI)/L in erlenmeyer flasks and vibrated by a shaker at 300 rpm during 0-200 minutes. Cr(VI) concentrations were measured using a spectrophotometer at 540 nm. The results showed that the maximum capacity of biosorption was approximately 5.13 mg/g. Estimation of biokinetic parameter, k1 was 0.015 minute-1 with a correlation coefficient of 0.91. It was concluded that the amount of P. chrysosporium biomass affected the equilibrium concentrations of Cr(VI) ions. The biosorption kinetics of Cr(VI) ion followed the equation of first order reaction.